2006
DOI: 10.1161/01.hyp.0000199192.17126.d4
|View full text |Cite
|
Sign up to set email alerts
|

Weather-Related Changes in 24-Hour Blood Pressure Profile

Abstract: Abstract-A downward titration of antihypertensive drug regimens in summertime is often performed on the basis of seasonal variations of clinic blood pressure (BP). However, little is known about the actual interaction between outdoor air temperature and the effects of antihypertensive treatment on ambulatory BP. Key Words: blood pressure monitoring, ambulatory Ⅲ hypertension Ⅲ aging S everal studies have reported that blood pressure (BP) values obtained both in the clinic and in ambulatory conditions are lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(91 citation statements)
references
References 32 publications
1
79
1
10
Order By: Relevance
“…Second, previous studies have examined the association between cold temperature and BP levels and BP variability by assessing their absolute levels. 13,15,16 In contrast, the study by Murakami et al has revealed an association between the difference in outdoor temperature between the coldest and warmest days and the difference of prewaking morning BP increase between the coldest and warmest days. This point deserves to be mentioned, because a recent study demonstrated that an increased risk for CVDs in association with cold temperature was more relevant in the context of an unexpected temperature decrease than in terms of the absolute temperature level itself.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Second, previous studies have examined the association between cold temperature and BP levels and BP variability by assessing their absolute levels. 13,15,16 In contrast, the study by Murakami et al has revealed an association between the difference in outdoor temperature between the coldest and warmest days and the difference of prewaking morning BP increase between the coldest and warmest days. This point deserves to be mentioned, because a recent study demonstrated that an increased risk for CVDs in association with cold temperature was more relevant in the context of an unexpected temperature decrease than in terms of the absolute temperature level itself.…”
mentioning
confidence: 85%
“…[13][14][15] This influence is not limited to office measurements but affects daily values (that is, home BP and ambulatory BP) as well. 15 Moreover, Modesti et al 16 recently examined the association between air temperature and ambulatory BP profile: they showed that cold temperature was significantly associated with excessive sleep-through MS in elderly persons, even when they were treated with a higher number of antihypertensive drugs in cold weather. This cold temperature-augmented morning BP increase may partly account for the increased number of CVDs on cold mornings during the winter season.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although carried out on biased groups (members of different summer and winter populations that had been selected to attend hypertension clinics), ABP studies in Italy [2,3] found that, in summertime, night-time dipping was less evident and SBPs were slightly increased; it was only with day-time BP measurements that the summertime decrease was evident. The night-time SBP increase was particularly apparent in elderly subjects receiving antihypertensive medication (type not specified).…”
Section: Night-time Dippingmentioning
confidence: 99%
“…Ambulatory blood pressure (ABP) recordings often reveal a small dip in BP values when subjects are resting at night (Fedecostante et al, 2012). In Italy, Modesti et al (2006) reported that in summer this night-time dipping was less evident, and systolic values (SBPs) were slightly increased; it was only with day-time BP measurements that the summer decrease was evident. They cautioned that 'the results of our study clearly indicate that the practice of reducing treatment in the summer in the elderly based on low clinic BP values is not good, because it might be responsible for a potentially dangerous increase in night BP.'…”
Section: Introductionmentioning
confidence: 99%